CHALLENGES OF HALAL CERTIFICATION FOR TRADITIONAL FOOD MSMEs: A CASE STUDY OF HALUA KENARI D&J - Sapsuha, Mubasysyyratul Ummah; Sapa, Nasrullah bin; Muthiadin, Cut (Tadayun: Jurnal Hukum Ekonomi Syariah, 2025)
Abstract This study examines the challenges faced by traditional food MSMEs in implementing halal certification in an island-based region, using the Halua Kenari D&J enterprise in North Maluku as a case study. Employing an empirical legal research design within a socio-legal framework, the research integrates a statutory approach with a case study method. Data were collected in Wailau Village, Sula Islands, through in-depth interviews, direct observation, and document review to assess absolute compliance with the Halal Product Assurance Law. The findings reveal a significant gap between regulatory standards and on-the-ground conditions. The main obstacles include: (1) technical barriers, such as production facilities that are integrated with household living areas; (2) administrative barriers, particularly inconsistencies in raw-material documentation; and (3) structural barriers, including the absence of halal assistance infrastructure at the village level. The study concludes that current halal regulations are not yet fully inclusive for rural MSMEs. Decentralized assistance services and targeted facility-improvement incentives are needed to bridge these gaps. Abstrak Penelitian ini mengkaji tantangan yang dihadapi UMKM pangan tradisional dalam mengimplementasikan sertifikasi halal di wilayah kepulauan, dengan studi kasus pada usaha Halua Kenari D&J di Maluku Utara. Menggunakan jenis penelitian hukum empiris (socio-legal research), penelitian ini memadukan pendekatan perundang-undangan dengan metode studi kasus. Pengumpulan data dilakukan di Desa Wailau, Kepulauan Sula, melalui wawancara mendalam, observasi langsung, dan telaah dokumen untuk menilai realitas kepatuhan terhadap UU Jaminan Produk Halal. Temuan penelitian menunjukkan adanya kesenjangan yang signifikan antara standar regulasi dan kondisi riil di lapangan. Hambatan utama meliputi: (1) kendala teknis, berupa fasilitas produksi yang menyatu dengan area domestik rumah tangga; (2) kendala administratif, khususnya inkonsistensi dokumentasi bahan baku; dan (3) kendala struktural, yakni ketiadaan infrastruktur pendampingan halal di tingkat desa. Penelitian ini menyimpulkan bahwa regulasi halal saat ini belum sepenuhnya inklusif bagi UMKM pedesaan. Diperlukan layanan pendampingan yang terdesentralisasi serta insentif perbaikan fasilitas yang tepat sasaran untuk menjembatani kesenjangan tersebut